1995
DOI: 10.1007/978-1-4899-1430-9
|View full text |Cite
|
Sign up to set email alerts
|

Theory and Application of Laser Chemical Vapor Deposition

Abstract: and fifth chapters respectively, show how these principles can be applied to model and understand various aspects of the pyrolytic and photolytic LCVD processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 0 publications
0
47
0
Order By: Relevance
“…Rohmund et al [20] reported LCVD of carbon nanotube films using a similar technique and experimental apparatus employed in [19]. Drawbacks associate with past LCVD techniques include: (1) the inability to control the size of metal particle catalysts, and (2) difficulties associated with controlling laser-induced gas phase reactions which complicate for scale-up production [15,16] and may potentially lower nanotube quality by gas phase contamination.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Rohmund et al [20] reported LCVD of carbon nanotube films using a similar technique and experimental apparatus employed in [19]. Drawbacks associate with past LCVD techniques include: (1) the inability to control the size of metal particle catalysts, and (2) difficulties associated with controlling laser-induced gas phase reactions which complicate for scale-up production [15,16] and may potentially lower nanotube quality by gas phase contamination.…”
Section: Introductionmentioning
confidence: 95%
“…The LCVD technique in general has several prominent advantages including high deposition rates of typically 100-1000 times greater than maximum rates obtained by plasma-enhanced CVD techniques, which is favorable for scale-up production of carbon nanotubes. Second, minimum substrate and grown nanotube damage is observed due to highly localized heating and excellent spatial resolution and process control [15][16][17]. Third, the open-air LCVD technique does not require a vacuum CVD chamber, which reduces the equipment needed and lowers the production cost.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, pigment (chromium (III) oxide) in the paint will be ejected into the gaseous domain from the paint surface. The reaction rate is approximated by Arrhenius equation (Mazumdar and Kar, 1995):…”
Section: Chemical Reactionmentioning
confidence: 99%
“…CVD involves in thermal decomposition or other chemical reaction of gas phase species, which occurs at elevated temperature, ranging from 500 to 1000 C. This CVD allows for deposition of target product using a substrate exposed into the volatile precursor as indicated above. Materials produced by CVD are highly diversified, including silicon, carbon nanotubes (CNTs) [140]. Materials with different elemental composition can be produced by CVD, such as silicon, carbon fiber, filament, silica (SiO 2 ) siliconegermanium (Si-Ge), tungsten (W), silicon carbide (SiC), titanium nitride (Ti 3 N 4 ), various high-K dielectrics, and synthetic diamond [138].…”
Section: Vapor Phase Depositionmentioning
confidence: 99%